Stereospecific Biotransformation Of 2,6,6 Trimethylcyclohex-2-Ene-1,4-Dione (Ketoisophorone) In A Non-Growing Whole Cell Saccharomyces Cerevisiae - Zakaria, Nur Zaherra (Universiti Sains Malaysia, 2017)
Biotransformation of ketoisophorone by non-growing cells was proposed from the study. The aim of this research is to investigate the effect of cofactor regeneration by using different yeast’s concentration and to investigate time courses for 2,6,6,-trimethycyclohex-2-ene-1,4-dione (ketoisophorone) to produce the corresponding intermediates of 2,6,6-trimethylcyclohexane-1,4-dione [(6R)-levodione] and 4-hydroxy-2,6,6-trimethylcyclohex-2-ene-1-one [(4S)-phorenol] as well as the main product, 4-hydroxy-2,6,6-trimethylcyclohexane [(4R,6R)-actinol] in a non-growing whole cell Saccharomyces cerevisiae. The liquid-phase biotransformation was carried out in shake-flask with buffer as the reaction medium at 37oC and 150 r.p.m using non-growing cells of S.cerevisiae. The cofactor regeneration of nicotinamide adenine dinucleotide coenzyme (NADH/NAD+) and its derivatives (NADPH/NADP+) was investigated using changes in ultraviolet-visible absorption spectra of these compounds. The spectrum of cofactor was monitored at 340nm wavelength and the sample was analysed for every one hour along the experiment. For the production of intermediates, (6R)-levodione has higher concentration as compared to the concentration of (4S)-phorenol due to the competition of coenzymes and higher rate of carbon-carbon double bond reduction compared to the reaction rate of carbonyl reduction.